2022
DOI: 10.1038/s42003-022-03557-9
|View full text |Cite
|
Sign up to set email alerts
|

Face identity coding in the deep neural network and primate brain

Abstract: A central challenge in face perception research is to understand how neurons encode face identities. This challenge has not been met largely due to the lack of simultaneous access to the entire face processing neural network and the lack of a comprehensive multifaceted model capable of characterizing a large number of facial features. Here, we addressed this challenge by conducting in silico experiments using a pre-trained face recognition deep neural network (DNN) with a diverse array of stimuli. We identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 61 publications
(77 reference statements)
2
20
0
Order By: Relevance
“…As the use of ANNs in social neuroscience matures, we expect to see an even broader range of phenomena explored using this method ( Figure 2C ). To the extent that ANNs faithfully represent the functional principles of brain activity, they may serve as test beds for in silico experiments that could not be carried out on biological brains ( Wang et al ., 2022 ; Jain et al ., 2023 ).…”
Section: Applications Of Anns In Social Neurosciencementioning
confidence: 99%
“…As the use of ANNs in social neuroscience matures, we expect to see an even broader range of phenomena explored using this method ( Figure 2C ). To the extent that ANNs faithfully represent the functional principles of brain activity, they may serve as test beds for in silico experiments that could not be carried out on biological brains ( Wang et al ., 2022 ; Jain et al ., 2023 ).…”
Section: Applications Of Anns In Social Neurosciencementioning
confidence: 99%
“…Recent studies in humans have also shown hippocampal neurons that encode faces based on visual similarity but not on concept associations, showing region‐based feature coding (Cao et al, 2022; Wang et al, 2022). These studies may help to reconcile the discrepancy in pattern separation reported by previous studies (Leal & Yassa, 2018; Quian Quiroga, 2020, 2023).…”
Section: Examples Of Multi‐task Research Designsmentioning
confidence: 99%
“…Moreover, the feature space in the deep layer of DCNNs serves as a useful model for simulating neural processes in the medial temporal lobe of the human brain. For example, researchers have demonstrated that features extracted from natural face images using DCNNs can be used to observe the features encoded by neuronal activity in the medial temporal lobe utilized in face identity recognition ( 20 ). On the other hand, generative computational models can be utilized to manipulate the process of face personality trait judgment in humans ( 21, 22 ).…”
Section: Introductionmentioning
confidence: 99%